Barrierefreiheit für Arbeiten und Lernen - Schreiner, Timo; et al. (Lexikon Berufsbildung – Ein Nachschlagewerk für die nicht akademischen und akademischen Bereiche, 2015)

Barrierefreiheit – Voraussetzung für Inklusion - Schreiner, Timo; Pelikan, Eva (berufsbildung, Zeitschrift für Praxis und Theorie in Betrieb und Schule, 2012)

Diversität und Inklusion in sozialen, personenbezogenen Dienstleistungsorganisationen – Normalitätskonstruktionen im Horizont gesellschaftlicher Transformation - Schreiner, Timo; Köngeter, Stefan (Zeitschrift für Diversitätsforschung und -management, 2020)
Social service organizations as part of social work are expected to promote diversity and enable inclusion. At the same time, empirical analyses reveal that these organizations function as entities which produce normalization. This tension, however, was not used as an opportunity to investigate practices on diversity and inclusion in social service organizations in a systematic manner. This article presents the findings of a case study which analyzed how diversity and inclusion was interpreted and dealt within the organizational culture of a municipal organization of child and youth welfare. The findings show that in the organizational culture a mode of action emerged which is called normality-plus. This mode is characterized by the fact that otherness is integrated into the organizational culture, but, at the same time, the notion of normality is kept untouched.<br
Keywords: Qualitative social research; social service organizations; diversity and inclusion; normality; normality‐plus

Organisation-Biografie-Vielfalt: Zur Konstruktion sozialer Kategorien im Ver-hältnis biografischer und organisationaler Erfahrungen - Schreiner, Timo (Bildung, Biographie, Ungleichheit. Beiträge der Biografieforschung zum Ver-hältnis von Bildung und sozialer Ungleichheit, 2020)

Organization between Theory and Practice - Schreiner, Timo (Zeitschrift für Soziologie der Erziehung und Sozialisation, 2020)
CRIS-Team WoS Importer:2020-10-16

Stichwort: Barrierefreiheit - Schreiner, Timo; Pelikan, Eva (berufsbildung, Zeitschrift für Praxis und Theorie in Betrieb und Schule, 2012)